2018
DOI: 10.1021/acscatal.8b01156
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Catalytic Mechanism and Substrate Diversity for Macrocyclization of Pikromycin Thioesterase

Abstract: Polyketide synthases (PKSs) share a subset of biosynthetic steps in construction of a polyketide, and the offload from the PKS main module of specific product release is most often catalyzed by a thioesterase (TE). In spite of the fact that various PKS systems have been discovered in polyketide biosynthesis, the molecular basis of TE-catalyzed macrocyclization remains challenging. In this study, MD simulations and QM/MM methods were combined to investigate the catalytic mechanism and substrate diversity of pik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…In short, the nucleophilic attack to the formation of tetrahedral intermediate was determined to be the ratedetermining step, and the energy barrier was also in good agreement with that reported energy barrier of picromycin TE-catalyzed macrocyclization [25]. These results indicated that the macrocyclization catalyzed by NYS TE with its natural substrate Nys could favorably take place in both thermodynamic and kinetic aspects.…”
Section: Nys-te Systemsupporting
confidence: 82%
See 2 more Smart Citations
“…In short, the nucleophilic attack to the formation of tetrahedral intermediate was determined to be the ratedetermining step, and the energy barrier was also in good agreement with that reported energy barrier of picromycin TE-catalyzed macrocyclization [25]. These results indicated that the macrocyclization catalyzed by NYS TE with its natural substrate Nys could favorably take place in both thermodynamic and kinetic aspects.…”
Section: Nys-te Systemsupporting
confidence: 82%
“…The transition state TS1 was located at the d 1 =1. To sum up, the whole energy barrier of the cyclization was 14.0 kcal/mol, which is similar to the barrier (16.3 kcal/mol) of 10-deoxymethynolide macrocyclization catalyzed by picromycin TE [25]. These results indicated that AMB-TE can easily catalyze this macrocyclization with its natural substrate Amb.…”
Section: Amb-te Systemsupporting
confidence: 64%
See 1 more Smart Citation
“…32 In our recent papers, the pre-reaction states (PRSs), complexes of the substrate and the active site reactant, were successfully used to understand the substrate diversity of thioesterase. 33,34 Here, the pre-reaction state (PRS) is also employed to understand the effects of R882H mutation on DNMT3A methylation. In practice, the pre-reaction state is dened as the product of the nucleophilic attack of Cys710 on cytosine.…”
Section: Introductionmentioning
confidence: 99%
“…Since the transition states of enzyme catalysis were hard to obtain in silico, we chose pre-reaction state (PRS) as an evaluation indicator. According to our previous research [ 26 , 36 ], PRS was the very prior stage of macrocyclization in terms of both structure and energy, and its formation was decisive to TE cyclization. The proportion of PRS was regarded as the degree of reaction readiness.…”
Section: Discussionmentioning
confidence: 99%